Avaliação de segurança em barragem de terra, sob o cenário de erosão tubular regressiva, por métodos probabilísticos: o caso UHE São Simão - Josias Eduardo Rossi Ladeira (2007)
The research describes the safety assessment for an embankment dam under the scenario of hypothetical backward erosion piping by probability methods, the case study being the embankment dam of the São Simão hydropower plant, in southcentral Brazil. The results identified critical points that justify more attention and prevention actions in order to avoid environmental impacts of embankment dam accidents. The performance methods for assessing the relative likelihood of piping failure was done by performance analysis and as a checked on event tree analysis (ETA), in order to assess the safety for embankment dam in study. The likelihood assessment of piping from the embankment took into account the dam zoning, filters, age of the dam, core soil types, compaction, foundation geology, dam performance, and monitoring and surveillance for 29 years of operation. The method involves the adjustment of the historical average probabilities of the three modes of progressive backward erosion: piping through the embankment, piping through the foundation and piping from the embankment into the foundation, by historic failures. The methods employed in this research are referred to as the UNSW method (University of New South Wales) and the ETA (Event Tree Analysis) method. The data base used to qualify the historical failures is composed by 1462 dams, which correspond to approximately 13% of world population of existing dams until 1982. The historical annual probability of failure of large embankment dams was estimated in 4,5 x 10-4 per dam per year, which is coherent the research results.